PARALINGUISTIC ANALYSIS OF UNITED NATIONS DOCUMENTS: THE ROLE OF NON-VERBAL AND GEOGRAPHICAL FEATURES IN DIPLOMATIC COMMUNICATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
United Nations (UN) documents represent one of the most influential forms of institutional communication in contemporary international relations. While previous studies have primarily focused on lexical, syntactic, and pragmatic characteristics of diplomatic discourse, comparatively little attention has been paid to paralinguistic features embedded within official documents. This article examines the role of paralinguistic and graphological elements in the construction of meaning within United Nations documentation. Drawing upon theories of discourse analysis, institutional communication, and paralinguistics, the study argues that visual and textual features—including typography, formatting conventions, punctuation patterns, capitalization, numbering systems, document structure, and multimodal components—contribute significantly to the interpretation of diplomatic texts.
Keywords: The article explores how these paralinguistic markers reinforce institutional authority, facilitate legal precision, signal diplomatic hierarchy, and shape reader interpretation. Through qualitative analysis of selected UN resolutions, reports, declarations, and meeting records, the study demonstrates that seemingly technical formatting choices perform communicative functions analogous to non-verbal cues in spoken interaction. The findings suggest that paralinguistic features constitute an essential yet understudied dimension of diplomatic discourse. The article concludes